Desain Kemasan “Aisyah Cake And Cookies” - Putri Noviani; Ariusmedi Ariusmedi (Journal of Creative Student Research, 2023)
"Aisyah cake and cookies" is a Micro, Small and Medium Enterprises or MSMEs in the field of culinary bakery, especially donuts in Padang and surrounding areas. The purpose of this Final Work is to design effective packaging and attract the attention of potential consumers so that the product can be known by the wider community and maximize the function of packaging that previously did not really protect the product to be better protected by the new packaging, as well as build trust from consumers that this product is safe, more hygienic and gives identity to the brand "Aisyah cake and cookies". In this design the author uses the 4D method which consists of Define, Design, Develop, and Disseminate. While the data analysis method used is SWOT analysis. This design will produce a packaging design for "Aisyah cake and cookies" in the form of packaging as the main media while posters, plastic bags, X banners, aprons, stickers, and Instagram feeds as supporting media.